Science-fiction et fiction scientifique en France : de Jules Verne à J.-H. Rosny aîné - Arthur B. Evans (ReS Futurae)
SF needs to be theoretically distinguished from its generic "cousin" Scientific Fiction. As an early example of the latter, Jules Verne's novels are structurally different from most SF. Verne's "Voyages Extraordinaires" were intentionally geared towards the pedagogical implantation offactual scientific knowledge. And the narratological blueprint of each "roman scientifique" in this series strongly reflects this intent. By examining diachronically the place and function of such "scientifically didactic discourse" in the works of certain French authors of the late 19th and early 20th centuries such as Verne, d'Ivoi, Le Rouge, Robida, and Rosny aine', one can discern a palpable evolution in the narrative recipes used. On the one hand, the deductive (and often reductive) passages of scientific pedagogy become progressively muted and supplanted by inductive hermeneutic structures which serve to enhance fictional verisimilitude. On the other, textual referentiality increasingly grows "oblique" and non-mimetic, more frequently affecting the reading process itself. It is through an investigation of these narratological phenomena that one can best differentiate Scientific Fiction from SF as well as witness the historical transmutation of the former into the latter.